Emerging sustainable facilities management practices in health-care sector. Issue 1 (21st January 2020) - Nazeer, Sabrina Fathima; Ramachandra, Thanuja; Gunatilake, Sachie; Senaratne, Sepani
Abstract : Purpose: Health-care (HC) is one of the most polluting industries and recognised as the second energy-intensive sector, emitting 8 per cent out of total 40 per cent of total carbon emissions. Integrating sustainability to facilities management operations is imperative and could significantly contribute to reducing energy consumption, waste and day-to-day operational costs of buildings. The integration of sustainability into FM practices depends on factors such as facility type, organisational scale, business sector and organisation characteristics. This paper aims to explore the SFM practice with a specific focus on HC-specific FM services and respective sustainable practice that could be integrated into FM operations. Design/methodology/approach: A Delphi survey was administered to ten experts in two rounds, who are specialised in FM and sustainable practices in the HC sector. Data gathered from the survey were analysed using the Relative Importance Index to identify the most significant FM services and sustainable practices. Findings: The study found 9 significant FM services and 49 sustainable in HC. The top three significant FM services include "building services (BS)", "space planning (SP)" and "quality management (QM)". Further, "identifying applications for energy-saving measures" and "ensure onsite, off-site storage and transport of wastes" were found as the topmost significant sustainable practices. The relevancy of these identified sustainable practices to the principles of sustainability was determined. The results showed that 22, 18 and 09 sustainable practices were relevant to environmental, social and economic principles of sustainability, respectively. Originality/value: There is a dearth of literature that integrates sustainable FM practices in HC sector, and this study fulfills this research gap. The study is novel in offering a framework to integrate sustainability into FM practice in HC sector.